Narasi Keadilan dan Emosi Sosial dalam Pemberitaan Kematian Affan Perspektif Retorika Aristoteles - Dede Putri; Desma Yuliadi Saputra; Rina Andriani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
The news of the death of Affan Kurniawan, an online motorcycle taxi driver who lost his life in clashes during demonstrations in Jakarta, sparked an extraordinary public reaction and gave rise to the narrative of "Justice for Affan." This information not only conveyed facts but also shaped the construction of justice and social emotions through media rhetorical techniques. This study aims to analyze how the narrative of justice and social emotions was formed in the reporting of Affan's death, using the perspective of Aristotle's rhetoric, which consists of Ethos, Pathos, and Logos. The method applied was descriptive qualitative analysis, focusing on news texts from the international news portal The Straits Times. The results of the analysis indicate that Ethos was constructed through the selection of sources deemed credible, such as the victim's family and official statements from authorities; Pathos was reflected in the use of emotional language, depictions of grief, and representations of public anger; while Logos was demonstrated through the presentation of the sequence of events and supporting evidence. These findings indicate that reporting is not merely neutral but uses rhetorical strategies to create empathy, solidarity, and demands for justice among the audience. Thus, this analysis underscores the importance of rhetoric in mass media in influencing public perceptions and social reactions to tragic events.